Industrial training report: Prism Integrated Sdn Bhd / Mohamad Azran Aziz - Aziz, Mohamad Azran (Perpustakaan Tengku Anis, 2017)
The report is about the practical training session of internship student named Mohamad Azran Bin Aziz at Prism Integrated Sdn Bhd In this report, there have a four chapter. The first chapter will cover on basic details regarding the organization, such as the company profile. In order to figure out the size of the company, organization chart has been included in this chapter. Apart from that, the service and products offered by the organization is also included. The second chapter will cover about the departmental structure and the function of each department in Prism. Next chapter is about activities being done during the industrial training process at Prism. This chapter will show the workflow and process regarding all the activities being done during the practical session. In the other section, special project will be presented at the end of this chapter. The last chapter is about the reflection on the experience and the opportunities given to an Internship student during the internship. This chapter will cover on the application of knowledge, skill and experiences that the students has applied Furthermore, this chapter will touch on the student's personal thoughts and opinion on the working environment gained from the practical place. Lastly is on the limitation and recommendation for the entire aspects seen during the five months internship in all departments' rotation.